Where you once belonged : a novel - Haruf, Kent (Vintage Contemporaries, 2000)
Former high-school football hero Jack Burdette returns to his hometown eight years after he had left, but his one-time pranks and high-spirited high jinks have turned into crimes--with terrifying consequences for the people of Holt County.